Pengaruh Penambahan Additive Retarder terhadap Thickening Time Slurry Cement Class G pada Sumur D31 Lapangan Turangan - Dandi Turangan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Well cementing is a critical stage in drilling operations to ensure well integrity and prevent fluid migration between formations. The problem addressed in this study is the effect of retarder contamination on the thickening time of cement slurry under high temperature and pressure conditions. The objective of this research is to analyze changes in thickening time due to variations in retarder concentration at a Bottom Hole Circulating Temperature (BHCT) of 270°F. Previous studies indicate that retarders delay cement setting and are influenced by composition and temperature. The method used is a quantitative experimental approach employing an HPHT Consistometer with three retarder variations. The results show that increasing retarder concentration extends the thickening time. In conclusion, proper control of retarder concentration is essential for slurry performance. Further research is recommended to investigate combinations of additives and a wider range of well conditions.